Using academic performance indicator to evaluate the cost to company of management graduates - Kapse, Manohar; Kaul, Natasha; Poulose, Jeanne; Sharma, Vinod; Bhattacharjee, Sanjib (London : SAGE Publications: SAGE Business Cases Originals, 2024)
As the placement season hits CBS Business School, India, the pressure to get placed is at its peak. As the placement season draws to a close, the unplaced students storm the Director’s office complaining about unfair treatment in the process. They lay blame on the random shortlisting followed by the Placement co-ordinator. Concerned with these allegations, the Director calls on faculty to investigate the situation. During the conversation one of the students, Rachit, expresses regret in not focusing solely on academics and instead on developing a more well-rounded profile. He feels that that is the reason for his failure to get placed. A fundamental question arises of how closely academic performance and Cost to Company are related. Data is collected to examine the validity of the long-held belief that higher academic performance leads to higher paying job placement.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Management -- Study and teaching -- India -- Case studies